Differential expression of angiotensin-converting enzyme-2 in human paranasal sinus mucosa in patients with chronic rhinosinusitis. Issue 9 (30th September 2021) - Kawasumi, T; Takeno, S; Nishimura, M; Ishino, T; Ueda, T; Hamamoto, T; Takemoto, K; Horibe, Y
Abstract: Objective: Severe acute respiratory syndrome coronavirus-2 uses angiotensin-converting enzyme-2 as a primary receptor for invasion. This study investigated angiotensin-converting enzyme-2 expression in the sinonasal mucosa of patients with chronic rhinosinusitis, as this could be linked to a susceptibility to severe acute respiratory syndrome coronavirus-2 infection. Methods: Ethmoid sinus specimens were obtained from 27 patients with eosinophilic chronic rhinosinusitis, 18 with non-eosinophilic chronic rhinosinusitis and 18 controls. The angiotensin-converting enzyme-2 and other inflammatory cytokine and chemokine messenger RNA levels were assessed by quantitative reverse transcription polymerase chain reaction. Angiotensin-converting enzyme-2 positive cells were examined immunohistologically. Results: The eosinophilic chronic rhinosinusitis patients showed a significant decrease in angiotensin-converting enzyme-2 messenger RNA expression. In the chronic rhinosinusitis patients, angiotensin-converting enzyme-2 messenger RNA levels were positively correlated with tumour necrosis factor-α and interleukin-1β (r = 0.4971 and r = 0.3082, respectively), and negatively correlated with eotaxin-3 (r = −0.2938). Angiotensin-converting enzyme-2 immunoreactivity was mainly localised in the ciliated epithelial cells. Conclusion: Eosinophilic chronic rhinosinusitis patients with type 2 inflammation showed decreased angiotensin-converting enzyme-2 expression in their sinus mucosa. Angiotensin-converting enzyme-2 regulation was positively related to pro-inflammatory cytokines, especially tumour necrosis factor-α production, in chronic rhinosinusitis patients.